2017
DOI: 10.3329/bjvm.v14i2.31401
|View full text |Cite
|
Sign up to set email alerts
|

Haemato-Biochemical Alterations as Biomarkers of Lead Induced Toxicity in Male Wistar Rats

Abstract: The present work is devoted to access some of the biomarkers due to lead toxicity in experimental Wistar male rats orally exposed to graded doses of lead (200, 300 and 400 ppm of lead as lead acetate) over a period of four, eight and twelve weeks. A total of sixty Wistar male rats were equally divided into four groups A, B, C and D. Group A served as control. Groups B, C and D were exposed to 200, 300 and 400 ppm of lead as lead acetate respectively. At the end of four, eight and twelve weeks, five animals eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…The result of this study shows accumulation of lead in the blood upon absorption, this is due to affinity of lead for red blood cells which transport them to various parts of the body and soft tissues where they are stored and results in perturbation of metabolic processes. Our results is consistent with other workers Warren, et al [4], Murata, et al and Okediran, et al reported blood lead accumulation following oral exposure resulting in loss of weight, inhibition of haem synthesis and reduction of packed cell volume [16,17].…”
Section: Discussionsupporting
confidence: 93%
“…The result of this study shows accumulation of lead in the blood upon absorption, this is due to affinity of lead for red blood cells which transport them to various parts of the body and soft tissues where they are stored and results in perturbation of metabolic processes. Our results is consistent with other workers Warren, et al [4], Murata, et al and Okediran, et al reported blood lead accumulation following oral exposure resulting in loss of weight, inhibition of haem synthesis and reduction of packed cell volume [16,17].…”
Section: Discussionsupporting
confidence: 93%
“…Most increases BUN and creatinine levels are caused by kidney damage. [9] The current work showed an increase in the levels of a BUN and creatinine in lead acetate-treated rat in comparison to the control and this may be due to the degeneration of renal cell by necrosis which causes leakage of these BUN and creatinine into blood circulation. The similar observation has reported that lead acetate treatment induced significant elevation of serum BUN and creatinine activities.…”
Section: Discussionmentioning
confidence: 62%
“…It has been reported that the lead toxicity condition can cause excessive production of ROS, there is an imbalance between the production of oxidants and the defense systems of antioxidant which may promote the induction of lipid peroxidation, proteins and DNA damage, leading to renal cell death via apoptosis or necrosis. [789] Expression of the caspase-3 is a hallmark of apoptosis and can be used in cellular assays to quantify activators and inhibitors of the “death cascade.”[8] The results of this study showed that the expression of caspase 3 of kidney tissue was significantly increased on the lead acetate group. Dose-dependent manner of chitosan- P. merkusii extract nanoparticle decreased kidney tissue caspase 3 expression in lead acetate treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models with acute and chronic Pb exposure have shown decreased total and protein-bound sulfhydryl (SH) groups in homogenates and synaptosomes of the brain [8]. Pb intoxication in animals has revealed a significant decrease in serum total protein, albumin, and the A/G ratio [9,10]. The reduction of proteins was due to precipitation of soluble proteins, inhibition of protein biosynthesis through the specific enzymes in cell processes, and a decrease in free amino acid utilization for protein synthesis.…”
mentioning
confidence: 99%